Kitâbü’l-fasl fi’l-milel ve’l-ehvâ’ ve’ni-nihal - 880-01 İbn Hazm, 994-1064. (Mısır Mısır Mısır Mısır)
5 cilt 2 ciltte (1. c. 4, 224 sayfa, 2. c. 193, [5] sayfa, 3. c. 264 sayfa ; 4. c. 227 sayfa, 5. c. 144 sayfa)